Poly(vinyl alcohol) Hydrogels: The Old and New Functional Materials. (30th November 2021) - Wang, Menghan; Bai, Jianzhong; Shao, Kan; Tang, Wenwei; Zhao, Xueling; Lin, Donghai; Huang, Shan; Chen, Cheng; Ding, Zheng; Ye, Jiayi
Abstract : Hydrogels have three-dimensional network structures, high water content, good flexibility, biocompatibility, and stimulation response, which have provided a unique role in many fields such as industry, agriculture, and medical treatment. Poly(vinyl alcohol) PVA hydrogel is one of the oldest composite hydrogels. It has been extensively explored due to its chemical stability, nontoxic, good biocompatibility, biological aging resistance, high water-absorbing capacity, and easy processing. PVA-based hydrogels have been widely investigated in drug carriers, articular cartilage, wound dressings, tissue engineering, and other intelligent materials, such as self-healing and shape-memory materials, supercapacitors, sensors, and other fields. In this paper, the discovery, development, preparation, modification methods, and applications of PVA functionalized hydrogels are reviewed, and their potential applications and future research trends are also prospected.